Social welfare, inequality and deprivation - Brice Magdalou; Patrick Moyes (Luxembourg Income Study (LIS), 2008)
We provide a characterization of the generalised satisfaction - in our terminology nondeprivation - quasi-ordering introduced by S.R. Chakravarty (Keio Economic Studies 34 (1997), 17-32) for making welfare comparisons based on the absence of deprivation. We show that the non-deprivation quasi-ordering obeys a weaker version of the principle of transfers: welfare improves only for specific combinations of progressive transfers which require that the same amount be taken from richer individuals and allocated to one arbitrary poorer individual. We identify the subclass of extended Gini social welfare functions that are consistent with this principle and we show that the unanimity of value judgements among this class is identical to the ranking of distributions implied by the non-deprivation quasi-ordering. We extend the approach to the measurement of inequality by considering the corresponding relative and absolute ethical inequality indices.
Keywords: D31; D63; 330; Progressive Transfers; Welfare; Inequality; Deprivation; Lorenz Dominance; Extended Gini Social Welfare Functions; Soziale Wohlfahrtsfunktion; Einkommensumverteilung; Soziale Ungleichheit; Lorenz-Kurve; Gini-Koeffizient; Wohlfahrtsanalyse; Theorie